Morphometrical Analysis of Harderian Gland of Dove and Native Chickens - Magad, Ibtesm; Zghair, Fatimah Swadi (American Journal of Biomedicine and Pharmacy, 2025)
An important part of eye lubrication and immunological protection, the Harder's gland is a specialized tissue connected to the orbital region of birds. The local chicken (Gallus domesticus) and the laughing dove (Spilopelia senegalensis) are the two bird species whose Harder's gland morphological and morphometrical features are examined in this work. Gross analyses of the Harderian gland were performed on 20 chickens, adult roosters and 20 of which were adult male doves. The current investigation found that the rooster and doves have different bibbed Harderian gland sizes. It was discovered that the male rooster and doves have a larger Harderian gland in both length and width than the male rooster. Both the dove and the rooster had irregular lobule lumens. The rooster male's small acini were lined by low simple columnar epithelium, and their lumen was spherical. Still, only a few of them were elongated, and the cell boundaries were clearly visible.